2021
DOI: 10.1002/joa3.12624
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of left atrial abnormalities despite left atrial volume normalization after successful ablation of atrial fibrillation

Abstract: Background Left atrial volume index (LAVI) of >34 mL/m2 is the cutoff value for identifying an enlarged left atrium. The definition of left atrial (LA) reverse remodeling after atrial fibrillation (AF) ablation is undetermined. We hypothesized that patients with LA dilatation who achieve normal LA volume (LAVI<34 mL/m2) after AF ablation have better long‐term outcomes than those who do not. Furthermore, we investigated whether patients with a normal LA volume can also achieve normal LA function with AF ablatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
(119 reference statements)
0
6
0
Order By: Relevance
“…LA structural and functional cardiac abnormalities, including chamber dilatation and systolic/diastolic dysfunction, are all potential risk factors for AF [ 25 , 26 , 27 , 28 , 29 ]. Furthermore, LA structural and electrophysiological remodeling are key markers for risk stratification in patients with AF [ 1 , 26 , 27 , 28 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Left Atrial Structure and Function In Atrial Fibrillationmentioning
confidence: 99%
See 2 more Smart Citations
“…LA structural and functional cardiac abnormalities, including chamber dilatation and systolic/diastolic dysfunction, are all potential risk factors for AF [ 25 , 26 , 27 , 28 , 29 ]. Furthermore, LA structural and electrophysiological remodeling are key markers for risk stratification in patients with AF [ 1 , 26 , 27 , 28 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Left Atrial Structure and Function In Atrial Fibrillationmentioning
confidence: 99%
“…In a systematic review and meta-analysis, Njoku et al assessed whether LA volume was an independent predictor of AF recurrence following CA, and found that patients with AF recurrence following CA had a higher mean LA volume/LAVi compared with patients with no recurrence [ 31 ]. In contrast, many studies have revealed a reduction in LA enlargement after restoration of sinus rhythm by CA (reverse remodeling), and LA reverse remodeling was thought to be a marker for better outcomes (lower recurrence rate) of CA for AF [ 33 , 35 , 36 , 37 , 38 , 39 ]. In our recent work, we investigated whether the degree of LA volumetric reverse remodeling was associated with long-term outcomes (AF-free survival) after initial CA for AF in 140 patients with LA enlargement (LAVi ≥ 34 mL/m 2 ) at baseline [ 33 ].…”
Section: Left Atrial Structure and Function In Atrial Fibrillationmentioning
confidence: 99%
See 1 more Smart Citation
“…Catheter ablation can successfully eliminate the burden of AF, enabling structural reverse remodeling of the LA. 12 However, in a recent study of 140 patients with AF who underwent successful catheter ablation, it was concluded that abnormal LA pump and reservoir function persisted despite normalization of the LAVi to 34 mL/m 2 . 12 The results of this study suggested that patients with AF in whom sinus rhythm is successfully restored still have underlying substrate in the LA, and physicians should remain aware of the patient's risk for heart failure.…”
Section: The Left Atrium Is a Window To The Outcomes Of Patients With...mentioning
confidence: 99%
“…Therefore, numerous studies were conducted to identify the predictors of its recurrence. Most of these studies extensively focused on several LA factors, such as size [18][19][20][21][22] and function, [23][24][25][26][27] using multi-modality cardiac imaging. Generally, LA enlargement has been accepted as the most important and robust predictor of AF recurrence after ablation, and the LA diameter measured by echocardiography has been widely used due to its simplicity and universality.…”
Section: Predictive Value Of Pac/24 H After the Proceduresmentioning
confidence: 99%